Cadmium exposure, epigenetic modifications, and serum cystatin C: insights into mediated pathways and mortality risks in U.S. adults - Yu-Wei Fang; Ching-Way Chen; Ta-Chen Su; Chien-Yu Lin (Clinical Epigenetics)
Abstract Background Cadmium exposure has been linked to elevated cystatin C levels, disruptions in epigenetic patterns, and increased mortality risk. However, the role of epigenetic modifications in the relationship between cadmium and cystatin C remains poorly understood. Furthermore, it is unclear how cystatin C and epigenetic changes influence the connection between cadmium exposure and mortality outcomes. The study explored the associations among blood cadmium levels, serum cystatin C, an epigenetic biomarker (DNA methylation-predicted cystatin C, DNAmCystatinC), and mortality outcomes. Methods We utilized data from 8716 participants aged 18 years and older in the National Health and Nutrition Examination Survey (NHANES, 1999–2002), linked to mortality records from the National Center for Health Statistics (NCHS) through 2019. Results Our findings revealed that higher natural log-transformed (ln)-blood cadmium was associated with elevated ln-serum cystatin C (β = 0.052, P < 0.001) and higher ln-DNAmCystatinC (β = 0.007, P = 0.008). Compared to the reference group (both blood cadmium and DNAmCystatinC ≤ 50th percentile), those with blood cadmium and DNAmCystatinC > 50th percentile had the highest mean serum cystatin C levels (1.26 mg/L vs. 1.11 mg/L; P for trend = 0.002). Structural equation modeling (SEM) indicated that DNAmCystatinC partially mediated the relationship between cadmium exposure and cystatin C, with a total effect of 0.068, a direct effect of 0.066, and an indirect effect of 0.002. Weighted Cox regression analysis showed higher blood cadmium was associated with an increased risk of all mortality outcomes, with stronger associations observed in individuals whose serum cystatin C was at or above the 50th percentile. These findings were consistent both in the overall population and after excluding individuals with chronic kidney disease. Furthermore, a significant interaction was identified between blood cadmium and serum cystatin C in their influence on all-cause mortality. Conclusions We found higher blood cadmium is linked to increased serum cystatin C and DNAmCystatinC, with DNAmCystatinC partially mediating the effect on serum cystatin C. Notably, serum cystatin C may modify the relationship between cadmium exposure and mortality outcomes. Further research is warranted to elucidate these complex interactions.